Encyclopedia of Polymer Science and Technology 2003
DOI: 10.1002/0471440264.pst284
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphazenes

Abstract: An overview of polyphosphazene science is given. A brief history of over 100 years of synthetic developments is presented, from the work of Stokes to the latest cationic condensation polymerization, followed by discussions of blending, cross‐linking, and functionalization. Applications of polyphosphazenes as elastomers, solid polymer electrolytes, membranes, and flame retardants are reviewed. Biomedical research is referenced and hybrid polyphosphazenes and polymers containing cyclophosphazenes are also covere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 184 publications
0
1
0
Order By: Relevance
“…Fuel cell tests were carried out to compare beginning-of-life (BoL) and end-of-life (EoL) fuel cell power output after a carbon corrosion voltage cycling experiment for nanofiber 17 We have found that well-mixed PVDF/Nafion blends with nanometer-size domains can be prepared by electrospinning Nafion + PVDF mixtures. 18 The present paper does not deal with the chemistry/morphology of Nafion/PVDF blended fibers, (this topic will be addressed in separate publications), but only with the use of these blends as binders in hydrogen/air fuel cell cathodes.…”
mentioning
confidence: 99%
“…Fuel cell tests were carried out to compare beginning-of-life (BoL) and end-of-life (EoL) fuel cell power output after a carbon corrosion voltage cycling experiment for nanofiber 17 We have found that well-mixed PVDF/Nafion blends with nanometer-size domains can be prepared by electrospinning Nafion + PVDF mixtures. 18 The present paper does not deal with the chemistry/morphology of Nafion/PVDF blended fibers, (this topic will be addressed in separate publications), but only with the use of these blends as binders in hydrogen/air fuel cell cathodes.…”
mentioning
confidence: 99%